Living with Psychosis without Mental Health Services: A Narrative Interview Study. Issue 7 (19th July 2021) - McGranahan, Rose; Jakaite, Zivile; Edwards, Alice; Rennick-Egglestone, Stefan; Slade, Mike; Priebe, Stefan
Abstract : Objectives: Little research has looked at how people who do not use mental health services experience psychosis. Thus, the present study aimed to explore the experiences and views of people with psychosis who have neither sought nor received support from mental health services for at least 5 years. Design: A narrative interview study. Thematic analysis was used to analyse the data. Setting: England. Participants: Twenty-eight participants with self-defined psychotic experiences were asked to provide a free narrative about their experiences. Results: Five themes were identified: (1) Perceiving psychosis as positive; (2) Making sense of psychotic experiences as a more active psychological process to find explanations and meaning; (3) Finding sources of strength, mainly in relationships and the environment, but outside of services; (4) Negative past experiences of mental health services, leading to disengagement and (5) Positive past experiences with individual clinicians, as an appreciation of individuals despite negative views of services as a whole. Conclusions: Perceiving psychosis as something positive, a process of making sense of psychotic experiences and the ability to find external sources of strength all underpin—in addition to negative experiences with services—a choice to live with psychosis outside of services. Future research may explore to what extent these perceptions, psychological processes and abilities can be facilitated and strengthened, in order to support those people with psychosis who do not seek treatment and possibly also some of those who are in treatment.